2016
DOI: 10.19046/abp.v03i04.07
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Imatinib: A wonder drug in Oncology

Abstract: Imatinib is one of the first cancer therapies that has shown a potential for a novel approach in cancer treatment. Imatinib represents a therapeutic breakthrough as a targeted therapy in the form of selective tyrosine kinase inhibitors (TKIs) specifically BCR-ABL, c-KIT, PDGFRA. It has become the first line drug in management of several cancers. Apart from its remarkable success in CML, it has also shown promising results in the treatment of gastro-intestinal stromal tumors, clonal eosinophilic disorders, phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…4 Only a few (<5) spermatozoa present and no spermatids or spermatozoa present. 5 No spermatozoa, no spermatids but several or many spermatocytes present. 6 No spermatozoa and only a few spermatids (<5-10) present.…”
Section: Biochemical Analysis Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Only a few (<5) spermatozoa present and no spermatids or spermatozoa present. 5 No spermatozoa, no spermatids but several or many spermatocytes present. 6 No spermatozoa and only a few spermatids (<5-10) present.…”
Section: Biochemical Analysis Protocolsmentioning
confidence: 99%
“…3 It is also used in the treatment of CML and gastrointestinal tumors by targeting c-kit and PDGFR kinases. 4,5 The c-kit ligand stem cell factor (SCF) is involved in events such as chemotaxis, proliferation, differentiation and even survival by activating numerous pathways. 6 Previous studies reported that c-kit is expressed in primordial germ cells and by various cells during germ cell migration and that it can serve as a marker through involvement in cell selection and preservation during migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, imatinib, the first FDA approved tyrosine kinase inhibitor (YKI), has been recognized as an inhibitor of BCR–ABL, c-KIT and PDGFR. Because of its multiple activities, imatinib has found use beyond the original designation for the treatment of chronic myeloid leukemia (CML) ( 8 ). Thus, polypharmacologic YKIs have become a common approach in this arena as researchers have become less concerned over the lack of kinase selectivity ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%